Developmental toxicity of triclocarban in zebrafish (Danio rerio) embryos. Issue 5 (18th January 2019) - Shi, Qimeng; Zhuang, Yuhang; Hu, Tingting; Lu, Chuncheng; Wang, Xinru; Huang, Hongyu; Du, Guizhen
Abstract: Triclocarban (TCC), which is used as an antimicrobial agent in personal care products, has been widely detected in aquatic ecosystems. However, the consequence of TCC exposure on embryo development is still elusive. Here, by using zebrafish embryos, we aimed to understand the developmental defects caused by TCC exposure. After exposure to 0.3, 30, and 300 μg/L TCC from 4‐hour postfertilization (hpf) to 120 hpf, we observed that TCC exposure significantly increased the mortality and malformation, delayed hatching, and reduced body length. Exposure to TCC also affected the heart rate and expressions of cardiac development–related genes in zebrafish embryos. In addition, TCC exposure altered the expressions of the genes involved in hormonal pathways, indicating its endocrine disrupting effects. In sum, our data highlight the impact of TCC on embryo development and its interference with the hormone system of zebrafish.